Acute Respiratory Failure Is the Initial Manifestation in the Adult-Onset A3243G tRNALeu mtDNA Mutation: A Case Report and the Literature Review - Pan, Xiaoli; Wang, Lijun; Fei, Guoqiang; Dong, Jihong; Zhong, Chunjiu; Lu, Jiahong; Jin, Lirong (Frontiers in Neurology, 2019)
Isolated mitochondrial myopathy refers to the condition that mitochondrial disorders primarily affect skeletal muscle system. Here we reported a case who presented with acute respiratory failure as the initial and predominant clinical manifestation after using anesthetic drugs. The diagnosis of mitochondrial myopathy was made by histochemical findings of ragged red fibers with modified Gomori trichrome Stain in skeletal muscle biopsy and genetic detection of an A3243G point mutation in the tRNALeu (UUR) gene of mitochondrial DNA (mtDNA) in peripheral blood specimen. He revealed a benign clinical outcome by ventilator assistance and cocktail treatment. Further, we performed a literature review on patients with respiratory failure as the early and predominant manifestation in adult-onset isolated mitochondrial myopathy. Eleven cases in nine studies (including our case) have been reported, and five of whom underwent DNA analysis all harbored A3243G mutation in the tRNALeu gene of the mtDNA. Usage of sedative drugs tends to induce acute respiratory failure in such cases.